2017
DOI: 10.1177/1558944717701240
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Carpal Tunnel Release in Patients Receiving Workers’ Compensation: A Systematic Review

Abstract: WC patients undergoing carpal tunnel release (CTR) fare poorly as compared with non-WC patients in nearly every metric. Higher rates of postoperative pain with delayed return to work can be anticipated in a WC cohort. In addition, WC patients receive suboptimal preoperative workup, and it is possible that unnecessary surgery is being completed in these cases. These findings are important to consider when treating the WC patient with CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Mean RTW times ranged from 4-168 days in 41 studies; median RTW times ranged from 14-60 days in 17 studies. Earlier return to work was reported following endoscopic CTR and in populations without workers’ compensation, findings that are consistent with those of previous systematic reviews (59, 70). We also found that return to modified duties occurred sooner than return to full duties and return to non-manual occupations were generally faster than return to manual roles.…”
Section: Discussionsupporting
confidence: 91%
“…Mean RTW times ranged from 4-168 days in 41 studies; median RTW times ranged from 14-60 days in 17 studies. Earlier return to work was reported following endoscopic CTR and in populations without workers’ compensation, findings that are consistent with those of previous systematic reviews (59, 70). We also found that return to modified duties occurred sooner than return to full duties and return to non-manual occupations were generally faster than return to manual roles.…”
Section: Discussionsupporting
confidence: 91%
“… 6 The relationship between longer duration of work absence and availability of sick pay has also be reported previously for those with and without worker’s compensation. 9 21 It is plausible that financial necessity is driving earlier return to work for those with limited sick pay. Alternatively, those with access to paid leave might choose to take the maximum available duration.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the prognostic factors associated with return to work after CTR identified 11 studies which evaluated more than 90 potential prognostic factors. 8 Longer durations of work absence after CTR were found to be associated with: receipt of workers' compensation 9 ; manual work [10][11][12] ; longer expected durations of work absence 10 ; being on sick leave before CTR surgery 13 ; selfblame for the hand problem 13 and beliefs that the symptoms were caused by work. 12 Much of the existing research has been conducted at single sites and involved small numbers of participants.…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, patients with workers' compensation have higher rates of postoperative pain after CTR with delayed return to work, which may contribute to specific insurance requirements of EDS prior to surgery. 16 Moreover, 14 respondents typed in that insurance authorization or requirement was a reason behind obtaining EDS. Additionally, 47% of respondents stated concerns regarding malpractice as a reason for obtaining EDS.…”
Section: Discussionmentioning
confidence: 99%